Isolation and characterization of luteolin and ferulic acid from Plumbago auriculata cultivated in Iraq - Massara Nazar Ahmed; Amjed Haseeb Khamees (Iraqi Journal of Pharmaceutical Sciences)
Plumbago auriculata is a perennial plant belong to Plumbaginaceae family. It is an endemic genus of 18 species in South Africa. All plant parts have many phytochemical compounds appearing several pharmacological activities. The study was aimed to isolate and identify of the bioactive phenolic compounds (luteolin and ferulic acid) from Plumbago auriculata cultivated in Iraq by various chromatographic and spectroscopic techniques. The plant materials were defatted with n-hexane solvent by maceration for 48hr, and extracted by soxhlet apparatus using 85% methanol solvent, then fractionated with the solvents of petroleum ether, chloroform, and ethyl acetate. High performance liquid chromatography (HPLC) was used to identify luteolin and ferulic acid in the fraction of ethyl acetate. The identified compounds were isolated using analytical HPLC, then characterized and identified the isolated compounds using various detecting techniques including , HPLC by comparing with their standards and spiking, Fourier transform infrared spectroscopy (FTIR), in addition to the liquid chromatography mass spectrometry (LC-MS/MS). The results of spectroscopic techniques confirmed the existence of luteolin and ferulic acid in the fraction of ethyl acetate, as it concluded that the data for the isolated compounds were coincided with that reported for the compounds in literatures. These isolated polyphenolic compounds which have various pharmacological activities may demonstrate some of the therapeutic uses of P.auriculata plant.